Because Ladies Lie : Eliminating Vestiges of the Corroboration and Resistance Requirements from Ohio's Sexual Offenses - Falk, Patricia J. (2014)
The Ohio General Assembly has made considerable progress in modernizing the state’s rape laws, eliminating many of the substantive and procedural obstacles to the successful prosecution of criminals. Yet, Ohio’s contemporary sexual offense provisions include vestiges of both the corroboration and resistance requirements. More specifically, the corroboration requirement (1) still applies to the crime of sexual imposition and (2) is used as a grading factor in gross sexual imposition. The resistance requirement (1) has been eliminated from rape and gross sexual imposition, but not sexual battery and sexual imposition, and (2) the wording of the existing resistance-elimination provisions is legally inaccurate. Finally, (3) resistance language (i.e., “ability to resist”) appears in subsections of the rape, gross sexual imposition, and sexual battery statutes, causing confusion about whether physical resistance is required by victims of these offenses. Part II of this Article provides a brief overview of the four most important sexual offense statutes in Ohio—rape, sexual battery, gross sexual imposition, and sexual imposition—to provide the necessary backdrop for the subsequent analysis. Part III examines the vestiges of the corroboration requirement in Ohio’s sexual imposition and gross sexual imposition statutes and analyzes an Ohio Supreme Court opinion directly on point. This Part argues that the remnants of the corroboration requirement should be eliminated as an outmoded expression of victim unreliability in rape law and offers simple statutory reforms to finally rid Ohio’s sexual offenses of any corroboration requirement. Part IV analyzes three problem areas involving the resistance requirement’s persistence in Ohio’s sexual offenses, and proposes statutory modernization reworking the resistance-lifting language, incorporating such language into the sexual battery and sexual imposition statutes, and revamping incapacity provisions to focus on consent, not resistance. The Article concludes by arguing that Ohio’s rape and sexual assault statutes could be substantially modernized without massive legislative reworking. The proposed changes are relatively modest in scope and would be quite easy to enact. The symbolic and real-world consequences of doing so are substantial